Pengaruh Kualitas Pelayanan Ritel dan Atmosfir Gerai terhadap Loyalitas Pelanggan pada Minimarket Yomart Wanaraja 2 Garut - Wati Susilawati (Jurnal Wacana Ekonomi, 2016)
This research is entitled "The Influence of Retail Service Quality and Store Atmosphere on Customer Loyalty in Minimarket Yomart Wanaraja 2 Garut". This study consists of three variables, namely, retail service quality (X1), store atmosphere (X2), and customer loyalty (Y). In general, the purpose of this study is to determine the effect of retail service quality and outlet atmosphere on customer loyalty at Minimarket Yomart Wanaraja 2 Garut. The method used in this research is descriptive and associative methods. In this study, a sample of 96 people was obtained. Data collection techniques used in this research are literature research, questionnaires, interviews, and documentation studies. The data measurement scale used in this study is the interval scale. The data obtained from the results of the questionnaire were then processed using the validity test, reliability test, t test, correlation coefficient analysis, and determination coefficient and multiple regression analysis. Based on the results of research from multiple regression calculations, the results show that partially the quality of retail service and outlet atmosphere has an effect on customer loyalty so that H0 is rejected, meaning that retail service quality and outlet atmosphere affect customer loyalty.